Asymptotic distribution of eigenvalues and eigenfunctions of a nonlocal boundary value problem - Şen, Erdoğan; Štikonas, Artūras (Mathematical Modelling and Analysis, 2021)
In this work, we obtain asymptotic formulas for eigenvalues and eigenfunctions of the second order boundary-value problem with a Bitsadze–Samarskii type nonlocal boundary condition.